PENGARUH KINERJA DOSEN PEMBIMBING TERHADAP KUALITAS SKRIPSI MAHASISWA : Studi Kasus pada Mahasiswa Pendidikan Fisika 2016/2017 UIN Alauddin Makassar - Suarga Suarga; Andi Jusriana; Sri Ulfa (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to determine the performance of student supervising lecturers, to determine the quality of student thesis, to determine the effect of the performance of supervising lecturers on the quality of student thesis. This type of research is quantitative descriptive. The population of this study were all students of Physics Education Study Program Batch 2016/2017 Faculty of Tarbiyah and Teacher Training at Alauddin State Islamic University Makassar. The sampling technique used Stratified Random Sampling. The instrument used is a questionnaire to measure the performance of supervisors and the quality of student thesis. The results of the descriptive analysis show that the performance of the supervising lecturers is in the medium category, namely with a percentage of 58%. The quality of student thesis is in the medium category with a percentage of 71%. While the inferential analysis shows that tcount< ttable= 0.389 < 2.045 then Ho is accepted and Ha rejected. This means that there is no significant influence between the performance of supervising lecturers and the thesis quality of students of the 2017 Physics Education Study Program, Faculty of Tarbiyah and Teacher Training, Alauddin State Islamic University Makassar.